Congenital syphilis: a rare presentation of a forgotten infection - Hegde, Anusha; Srinivasan, Ranjini; Dinakar, Chitra (The Journal of Infection in Developing Countries, 2023)
Congenital syphilis (CS), a common but forgotten disease has a broad spectrum of clinical presentation. Vertical transmission of this spirochaetal infection from the pregnant mother to the foetus can result in varied manifestations ranging from asymptomatic infection to life- threatening conditions in the form of stillbirth and neonatal death. The haematological and visceral manifestations of this disease can closely mimic various conditions including haemolytic anaemia and malignancies. Congenital syphilis should be considered as a differential in any infant presenting with hepatosplenomegaly and haematological abnormalities even if the antenatal screen was negative. We report a 6-month-old infant with congenital syphilis presenting with organomegaly, bicytopenia and monocytosis. A strong index of suspicion and early diagnosis is the key to the good outcome as treatment is simple and cost- effective.